CREDIT OPERATIONS OF BANKS AND CREDIT LINE - Юлія Владика; Анна Бегченкова (Економіка та суспільство, 2023)
The article reveals the essence of the concept of credit as an economic category, its forms, types and principles. The essence of the credit policy of banking institutions is defined, the credit operations of banks at the current stage of the economy are characterized, and the current state of the credit activity of Ukrainian banks is analyzed. The development of the financial services market in the conditions of the global financial crisis is analyzed. The problems and prospects of the development of the credit services market in Ukraine have been identified. The choice of credit strategy by banks of Ukraine was studied. The main problems of banks' lending activities are summarized and practical recommendations for overcoming them are provided. Ways to improve the credit process of commercial banks are predicted. Global practice proves that credit and credit operations permeate all spheres of society and contribute to the development of the country.